Civil Authority in the Byzantine Provinces (7th–9th Centuries) - Malatras, Christos (Studia Ceranea, 2024)
The issue of the rise of the thematic system of administration sparked off an intense debate that has engaged scholars for the past few decades. Those inclined to the view of a one-time reform have argued that the themata formed administrative units into which the Byzantine state was divided in the 7th century, and that the strategoi, who served as governors and commanders of particular themata, combined civil and military authority. However, it now seems that the changes in provincial administration were gradual, having been implemented over a period of more than three centuries. At some point in time, army units became permanently based in specific areas which evolved into military districts and which were then referred to by the names of those units. At the same time, the system of the Late Roman provinces headed by the praetorian prefects, the proconsuls and the praesides/consulares (archontes) continued to operate until the dawn of the 8th century. These officials must have retained at least some of their civil-judicial functions, since the state finances had been centrally administered by the mid-7th century. However, during that period, the military officials began to play an increasing role in civil administration, which affected not only the power held by the old civil officials, but also the extent to which their activity was reflected in primary sources.From the 730s to the 750s Leon III and Konstantinos V introduced a number of reforms that consolidated the new system. The emperors dissolved the old provinces (most likely altogether) and abolished the office of provincial governor. At the same time, the terms thema and strategia, which were used synonymously, began to appear on various seals. Soon after that, the entire civil administration was re-organized along thematic lines. New officials were appointed (protonotarios, chartoularios, anagrapheus, etc.) to control the finances of the themata. However, judicial authority was left in the hands of the military governors. A century later, after a period of internal turmoil, possibly during the reign of Theophilos (829–842), the government appointed new judicial officials with a view to undermining the power of the strategos. These new officials were initially referred to by classicizing names (anthypatos, praitor). By the early 10th century, the Greek title krites (judge) had become dominant.